Evaluation of Multiple Intelligence Theory in Arabic Language Learning - Namiyah Fitriani; Rinda Eka Mulyani; Sintya Rahma Dewi; Ikhwanul Habib; Ihsan Zikri; Rima Ayu Handayani (Journal Of Social Siences And Islamic Studies (JOSIS), 2025)
The background of this study is rooted in the pedagogical debate between the traditional IQ-based approach and Howard Gardner's Multiple Intelligences (MI) theory, which highlights the need for a more inclusive educational paradigm, particularly in the context of Arabic language learning where conventional methods often fail to accommodate learners' diverse intelligence profiles. The purpose of this study concludes that the application of authentic assessment based on Multiple Intelligences (MI) Theory in Arabic language education to improve learning outcomes through an approach that considers the diversity of students' abilities. Using a descriptive-qualitative literature study method based on the theoretical framework of Multiple Intelligences, this research analyzes the literature related to the implementation of MI and its assessment strategies in the context of Arabic language pedagogy. The results reveal that the MI-based approach significantly improves learning outcomes through tailoring materials to students' dominant intelligences, although its implementation faces challenges in a rigid education system. In conclusion, this study confirms that MI theory offers a value framework for creating more engaging and effective Arabic language learning, by recommending the integration of MI principles in existing teaching methods as well as the need for teacher training in the identification of MI profiles and the development of diversified assessment instruments